2011
DOI: 10.1002/ijc.25806
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of signal transducer and activator of transcription 5 by the inhibitor of janus kinases stimulates dormant human leukemia CD34+/CD38 cells and sensitizes them to antileukemia agents

Abstract: To verify molecular mechanisms by which leukemia stem cells (LSCs) maintain a dormant state, we explored the activity of the major prosurvival signal pathways in CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…1E). Further experiments found that the levels of DNMT3A in CD34 + /CD38 − AML cells with an abundant amount of p-STAT5 [6] isolated from patients (n = 8) were 2.8-fold greater than those in their CD34 + /CD38 + counterparts (P = 0.1) (Supplemental Fig. 1).…”
Section: Downregulation Of Stat5a Decreased Levels Of Dnmt3amentioning
confidence: 92%
See 1 more Smart Citation
“…1E). Further experiments found that the levels of DNMT3A in CD34 + /CD38 − AML cells with an abundant amount of p-STAT5 [6] isolated from patients (n = 8) were 2.8-fold greater than those in their CD34 + /CD38 + counterparts (P = 0.1) (Supplemental Fig. 1).…”
Section: Downregulation Of Stat5a Decreased Levels Of Dnmt3amentioning
confidence: 92%
“…Interestingly, CD34 + /CD38 − cells expressed a greater amount of signal transducer and activator of transcription 5 (STAT5) than their CD34 + /CD38 + counterparts in 10 of 11 cases [6]. STAT5 is involved in various aspects of hematopoiesis, cell proliferation, differentiation, and cell survival [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…21 Among the genetic aberrations identified in hematologic malignancies are FLT3, JAK2 and the CDKs. The specific indications that may be suitable for these targets include (a) chronic lymphocytic leukemia, multiple myeloma and mantle cell lymphoma, where CDK inhibitors have shown preliminary clinical efficacy; (b) acute myeloid leukemia, where the FLT3-ITD mutation is present in B30% of the patients 9 and activated JAK2 is an emerging target in both circulating blasts and tumor stem cells; 22,23 and (c) myeloproliferative diseases where JAK2 lesions were identified in 450% of the patients. 24 In this study, we present the preclinical evaluation of a novel chemical entity, TG02, a small molecule that inhibits these oncogenic kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Different JAK2 inhibitors reduce viability of AML cell lines in vitro (59,60). However, clinical studies using the JAK2 inhibitor ruxolitinib resulted in only modest antileukemic efficacy in relapsed/refractory AML patients (26).…”
Section: Discussionmentioning
confidence: 99%